PECULIARITIES OF DIAGNOSIS AND TREATMENT OF THE ESOPHAGEAL FOREIGN BODIES (COINS) IN CHILDREN - CLINICOSTATISTICAL STUDY - Corneliu Toader; Miorita Toader; Iolanda Cristina Vivisenco (Amaltea Medical Publishing House, 2015)
Objective. The authors performed a clinical and statistical study on cases of esophageal foreign bodies, with particular reference to ingested coins, admitted and treated in the ENT Department of the "Grigore Alexandrescu" Emergency Hospital for Children, between 01.01.2006 - 01.08.2007. Method and materials. A retrospective study, involving the interpretation and corroboration of the clinical and paraclinical fi ndings of each case study. Results. Of all cases of foreign bodies, coins held the highest percentage; the average length of stay in hospital was 2 days; there were no cases of major complications (esophageal perforation, bleeding by intercepting a large vessel, mediastinitis); were also recorded particular cases that required special attention. Conclusion. All cases were approached and resolved by rigid endoscopy; shortening the time elapsed before presenting to ENT specialist facilitates the therapeutic approach, dramatically lowering the risk of complications; X-ray examination, although essential, can sometimes provide incomplete information, the diagnosis certainty being ensured only by endoscopy.